IscR Regulation of Type 3 Fimbriae Expression in Klebsiella pneumoniae CG43 - Lin, Tien-Huang; Tseng, Cheng-Yin; Lai, Yi-Chyi; Wu, Chien-Chen; Huang, Chun-Fa; Lin, Ching-Ting (Frontiers in Microbiology, 2017)
In Klebsiella pneumoniae, we have previously shown that IscR, an Fe–S cluster-containing transcriptional factor, plays a dual role in controlling capsular polysaccharide biosynthesis and iron-acquisition systems by switching between its holo and apo forms. In this study, the effect of IscR on type 3 fimbriae expression and biofilm formation was investigated. We found that production of the major subunit of type 3 fimbriae, MrkA, was increased in the ΔiscR and iscR3CA strains, a strain expressing a mutant IscR that mimics apo-IscR, at both the translational and transcriptional levels. Based on the fact that type 3 fimbriae expression is the major factor affecting biofilm formation, increased biofilm formation was also found in ΔiscR or iscR3CA, suggesting that holo-IscR represses biofilm formation. However, the repression of type 3 fimbriae expression by IscR is indirect. To further understand the regulatory mechanism of IscR, the effect of IscR on the expression of mrkHIJ, which encodes cyclic di-GMP (c-di-GMP)-related regulatory proteins that control type 3 fimbriae expression, was studied. We found that holo-IscR could directly repress mrkHI transcription, indicating that MrkHI is required for IscR regulation of type 3 fimbriae expression. Finally, deletion of iscR attenuated K. pneumoniae virulence in a peritonitis model of mouse infection, while the absence of the [2Fe–2S] cluster of IscR had no effect on K. pneumoniae virulence during infection. Taken together, our results demonstrate the underlying mechanism of the [2Fe–2S] cluster of IscR in controlling type 3 fimbriae expression and its effect on K. pneumoniae pathogenesis.